1994
DOI: 10.1002/jcb.240540113
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of bone marrow stromal cell differentiation by cytokines whose receptors share the gp130 Protein

Abstract: The bone marrow stroma consists of a heterogeneous population of cells which participate in osteogenic, adipogenic, and hematopoietic events. The murine stromal cell line, BMS2, exhibits the adipocytic and osteoblastic phenotypes in vitro. BMS2 differentiation was examined in response to cytokines which share the gp130 signal transducing protein within their receptor complex. Four of the cytokines (interleukin 6, interleukin 11, leukemia inhibitory factor, and oncostatin M) inhibited hydrocortisone-induced adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 71 publications
4
57
2
Order By: Relevance
“…Work with neutralizing antibodies showed that this was principally dependent upon their production of OSM, although IL-6 and LIF also contributed to the pro-osteoblastic actions. As detailed above, OSM had indeed previously been demonstrated to drive human and murine MSC commitment to mineralizing osteoblasts, 25,46,47 and LIF has similar effects.…”
Section: The Source Of Osm: Osteoblasts Macrophages T Cells and Malmentioning
confidence: 69%
See 1 more Smart Citation
“…Work with neutralizing antibodies showed that this was principally dependent upon their production of OSM, although IL-6 and LIF also contributed to the pro-osteoblastic actions. As detailed above, OSM had indeed previously been demonstrated to drive human and murine MSC commitment to mineralizing osteoblasts, 25,46,47 and LIF has similar effects.…”
Section: The Source Of Osm: Osteoblasts Macrophages T Cells and Malmentioning
confidence: 69%
“…As OSMR is expressed by mesenchymal stem cells (MSCs), it is likely that direct effects of OSM stimulate osteoblast differentiation and activity in both murine and human MSCs while reducing adipocyte formation in the same populations. 25,46,47 Some of the influences of OSM can be attributed to suppression of sclerostin as noted above; however, enhanced differentiation of osteoblasts and impaired adipogenesis occurs in primary osteoblast cultures and osteoblastic cell lines even when little sclerostin is detectable. This suggests some direct action on immature osteoblastic cells, as indicated by rapid effects on the expression of C/EBPa and PPARg.…”
Section: Osm Directs Stromal Cell Commitment To Osteoblastogenesismentioning
confidence: 98%
“…2). Adipocytes are more than inert energy depots, and adipose tissue is a biologically active organ that carries out important (Green et al 1985;Kawai et al 2007) Antiadipogenic in primary rat preadipocytes (Wabitsch et al 1996b) and in human adipocytes (Wabitsch et al 1996a) Insulin/IGF-1 Proadipogenic Proadipogenic in 3T3-L1 cells (Green et al 1985;Smith et al 1988 Inhibitory Antiadipogenic in 3T3-L1 (Kawashima et al 1991), human marrow (Keller et al 1993), and human preadipocyte cells (Meng et al 2001) LTF Controversial No effect on 3T3-L1 adipogenesis (Hogan et al 2005;White et al 2008) Proadipogenic in 3T3-L1 cells (Aubert et al 1998) Antiadipogenic in bone marrow stromal cells (Gimble et al 1994) NP Inhibitory Antiadipogenic in 3T3-L1 cells (White et al 2008) OSM Inhibitory Antiadipogenic in 3T3-L1 cells (Miyaoka et al 2006;White et al 2008), mouse embryonic fibroblasts (Miyaoka et al 2006), and human adipose-derived mesenchymal cells (Song et al 2007) physiological processes including energy homeostasis and whole-body insulin sensitivity. Attenuating adipose tissue expansion can result in pathologies including insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these cytokines, e.g. IL-1 and IL-6, have been reported to inhibit adipogenesis of cultured MSC or pre-adipocytes (62). In addition, activation of TAK1-NIK/NF-B signaling by IL-1 in combination with tumor necrosis factor-␣ was shown to suppress transactivation of peroxisome proliferator-activated receptor ␥2 and inhibit adipogenesis of MSC (63).…”
Section: Genementioning
confidence: 99%